Pembelajaran Qur’an Berdasarkan Klan: (Studi Kasus Pada Masyarakat Kampung Samate, Kepulauan Raja Ampat) - Yusuf, Muhamad; Mayalibit, M. Yasin Un. (POROS ONIM: Jurnal Sosial Keagamaan, 2020)
This study aims to find out about the traditional model of learning Qur’an based on clan which is applied with ritual religion that maintained by the community in Samate Village South Salawati District Raja Ampat Island. Using a qualitative research with a social phenomenology paradigm. The results of this study found that every fam or clan has the people who capable to teach the Qur’an to their family and also the availability of teachers in reading Qur’an in Samate Village are much enough if it seen from the number of fam or clan. The difference of learning technique between the teachers are caused by the factor of teacher education in developing religious education innovation more programmed. The policy in selecting the teachers leads to the kinship structure between teachers and students which is a tradition from generation to generation. The people there really maintain harmony even they have different teachers where it can create social stability among the community. The origin of learning Qur’an is where everyone in one family or clan in society who has the ability to read the Qur’an has the opportunity to developing Qur’an education even that person does not receive a formal education.